PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS KONSTRUKTIVISME PADA MATERI TRANSFORMASI GEOMETRI KELAS IX SMP - Jihan Humaira (Jurnal Edukasi dan Penelitian Matematika, 2021)
The purpose of this research is to develop interactive multimedia based on constructivism for geometry transformation material that was valid and practical. This multimedia can support student in learning to be more interesting and help visualize the material. The type of this research is Research and Development.This research used the plomp model.The plomp model consists of a preliminary research and development of prototype or prototyping phase. Research data were collected by observation, interviews and questionnaires.The results of this research, show that the interactive learning multimedia has very valid category with a validity level was 82,02% and has very practical category with a practicality level by student was 85,07% and the practicality level by teacher was 97,91%.Keywords– Constructivism, Transformation Geometry, Interactive learning multimedia, Plomp